Evolutionary adaptations to the hormonal regulation of vascular tissue development - Wei Xiao; Eline Verhelst; Ling Yang; Yuji Ke; Bert De Rybel (Proceedings of the National Academy of Sciences, 2026)
Vascular tissues provide long-distance transport and physical support in the vascular plant lineage, providing a significant adaptive advantage. Although the cross talk between auxin and cytokinin in promoting both vascular cell proliferation and differentiation has been well studied in angiosperms such as Arabidopsis thaliana , little is known about this regulation in other vascular plant lineages. Here, we found that unlike the hormonal cross talk found in all other species under study, the lycophyte Selaginella moellendorffii shows clear task separation, with auxin driving vascular cell proliferation only and cytokinin specifically triggering cell differentiation. Using a cross-species transcriptomics approach, we found that members of the AUXIN / INDOLE-ACETIC ACID ( AUX / IAA ) and CYTOKININ OXIDASE ( CKX ) gene families exhibited divergent expression patterns in response to auxin and cytokinin treatments. Despite these regulatory differences, we show that AUX/IAA and CKX proteins are functionally conserved between Arabidopsis and Selaginella. Taken together, our findings suggest an evolutionary adaptation to the hormonal regulation of vascular tissue development in which core protein functions are conserved, but regulatory circuits diverged in lycophytes.